Optimizing Student Conditions in Pre-Implementation of Project Based Learning in the Junior High School Mathematics Curriculum - Muhammad Mahfud Efendi; Windy Tunas Putri (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
The purpose of this study is to analyze the optimization of students' conditions (SC) in the pre-implementation of Project Based Learning (PjBL) in the Junior High School (JHS) mathematics curriculum. Optimizing student conditions is focused on activities, communication, and formulating mathematical concepts. While the subjects are students and teacher mathematics in three JHS in Batu – Malang – Indonesia. This research includes ex-post facto with a causal comparative study, because the incident happened in the past, and tries to find information about causal relationships in the implementation of PjBL in the JHS mathematics curriculum. Data obtained from documents, questionnaires, and interviews, then analyzed and described qualitatively. Based on the results of the analysis that the SC which includes activities, communication, and linking concepts, is a good category with an optimality of 69.2%, and the lowest is relating mathematical concepts (63.0%). This affects the achievement of learning objectives (LO), with an optimality of 87.3%. To improve this optimality, teachers develop teaching materials, mathematics learning objectives, and utilize school facilities and environment in learning